1967
DOI: 10.1071/ch9671115
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose crystal growth. III. The relative growth rates of faces and their effect on sucrose crystal shape

Abstract: Graphical projections of sucrose crystal structure along the three principal crystallographic axes are presented. The packing of sucrose molecules at crystal surfaces shown by these projections is important in determining the relative growth rates of the various faces and the manner in which these are influenced by impurities. Relative growth rates of eight principal forms of the sucrose crystal in pure sucrose solutions are compared with those in the presence of impurities. This shows that the dominant fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The growth retardant effect of raffinose was also seen to be slightly greater at lower temperatures. These results are in accord with the previous results of Smythe (1967b) and Binder and Murphy (1 982).…”
Section: Morphologysupporting
confidence: 96%
See 1 more Smart Citation
“…The growth retardant effect of raffinose was also seen to be slightly greater at lower temperatures. These results are in accord with the previous results of Smythe (1967b) and Binder and Murphy (1 982).…”
Section: Morphologysupporting
confidence: 96%
“…Both Murphy and Binder (1 982) and Smythe (1967b) found that the effects of raffinose varied with temperature over the range 303-333 K. It was also found that the growth retardant effect of raffinose was slightly increased at the lowest temperatures. Vaccari et al (1986) carried out a detailed crystallographic study on the theoretical surfaces and face by face growth kinetics for both single and twin crystals.…”
Section: Aiche Journalmentioning
confidence: 89%
“…Analysis of sucrose crystal growth under industrial conditions, including under the presence of impurities has been studied by many groups, with large amounts of information in works by Smythe [8][9][10] and Rocha and co-workers [11][12][13][14]. Vaccari and Mantovani have presented a general review of sucrose crystallization, which includes a useful discussion of the tendency to form liquid inclusions during growth of sucrose crystals [15].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to both type and density of adsorption sites, varying from form to form, kinetic effects are highly anisotropic and dramatic changes of crystal morphology can occur. Many papers concern the raffinose effects: the advancement rates of [0 0 1] steps on the {1 0 0} form [12] along with the overall growth rates [13][14][15][16] were measured and the adsorption models proposed.…”
Section: Introductionmentioning
confidence: 99%